Phase 1 Pharmacokinetic Study of AZD5718 in Healthy Volunteers: Effects of Coadministration With Rosuvastatin, Formulation and Food on Oral Bioavailability. Issue 3 (2nd December 2019) - Ericsson, Hans; Nelander, Karin; Heijer, Maria; Kjaer, Magnus; Lindstedt, Eva‐Lotte; Albayaty, Muna; Forte, Pablo; Lagerström‐Fermér, Maria; Skrtic, Stanko
Abstract: AZD5718 is a first‐in‐class small‐molecule anti‐inflammatory drug with the potential to reduce the residual risk of cardiovascular events after myocardial infarction in patients receiving lipid‐lowering statin therapy. Leukotrienes are potent proinflammatory and vasoactive mediators synthesized in leukocytes via 5‐lipoxygenase and 5‐lipoxygenase‐activating protein (FLAP). AZD5718 is a FLAP inhibitor that dose‐dependently reduced leukotriene biosynthesis in a first‐in‐human study. We enrolled 12 healthy men in a randomized, open‐label, crossover, single‐dose phase 1 pharmacokinetic study of AZD5718 to investigate a potential drug‐drug interaction with rosuvastatin, and the effects of formulation and food intake (ClinicalTrials.gov identifier: NCT02963116). Rosuvastatin (10 mg) were absorbed more rapidly when coadministered with AZD5718 (200 mg), probably owing to weak inhibition of hepatic statin uptake, but relative bioavailability was unaffected (geometric least‐squares mean ratio [GMR], 100%; 90% confidence interval [CI], 86%‐116%). AZD5718 pharmacokinetics were unaffected by coadministration of rosuvastatin. AZD5718 (200 mg) was absorbed less rapidly when formulated as tablets than oral suspension, with reduced relative bioavailability (GMR, 72%; 90%CI, 64%‐80%). AZD5718 absorption was slower when 200‐mg tablets were taken after a high‐fat breakfast than after fasting, but relative bioavailability was unaffected (GMR, 96%; 90%CI, 87%‐106%). In post hoc pharmacodynamic simulations, plasma leukotriene B4 levels were inhibited by >90% throughout the day following once‐daily AZD5718, regardless of formulation or administration with food. AZD5718 was well tolerated, with no severe or serious adverse events. These data supported the design of a phase 2a efficacy study of AZD5718 in patients with coronary artery disease.